2016
DOI: 10.1002/adhm.201500746
|View full text |Cite
|
Sign up to set email alerts
|

α‐Galactosidase‐A Loaded‐Nanoliposomes with Enhanced Enzymatic Activity and Intracellular Penetration

Abstract: Lysosomal storage disorders (LSD) are caused by lysosomal dysfunction usually as a consequence of deficiency of a single enzyme required for the metabolism of macromolecules, such as lipids, glycoproteins, and mucopolysaccharides. For instance, the lack of α-galactosidase A (GLA) activity in Fabry disease patients causes the accumulation of glycosphingolipids in the vasculature leading to multiple organ pathology. Enzyme replacement therapy, which is the most common treatment of LSD, exhibits several drawbacks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 42 publications
0
67
1
1
Order By: Relevance
“…PEG also provided improvement by increasing enzyme delivery and activity [398]. In the last decade, modification of liposomes with RGD peptides or lysosomotrophic agents has also shown promise, such as the case for α–galactosidase delivery by RGD-functionalized liposomes, or VPRIV®-loaded liposomes targeted by octadecyl-rhodamine B for Gaucher disease [399402]. …”
Section: Additional Approaches Toward the Optimization Of Lysosomamentioning
confidence: 99%
“…PEG also provided improvement by increasing enzyme delivery and activity [398]. In the last decade, modification of liposomes with RGD peptides or lysosomotrophic agents has also shown promise, such as the case for α–galactosidase delivery by RGD-functionalized liposomes, or VPRIV®-loaded liposomes targeted by octadecyl-rhodamine B for Gaucher disease [399402]. …”
Section: Additional Approaches Toward the Optimization Of Lysosomamentioning
confidence: 99%
“…26,27 Such structures have recently been studied by some of us as alternative nanocarriers to liposomes, thanks to their outstanding stability and capability of multifunctional activity. [28][29][30] Moreover, we have also recently demonstrated that extremely stable and bright fluorescent organic nanoparticles (FONs) for bioimaging can be obtained by incorporating hydrophobic fluorenyl-derived fluorophores within QS-membranes. 31 In these studies, it was shown that, upon incorporation in QSs, the fluorophores could be stably dispersed in water reducing the ACQ effect.…”
Section: Introductionmentioning
confidence: 99%
“…CHOL affects cellular processes by interacting with other membrane lipids and specific proteins, and also participates in several membrane trafficking and transmembrane signaling processes [6,7]. Outside the field of fundamental biology, CHOL is an important element in the development of new biomaterials; as a helper lipid in liposomes developed for drug delivery [8,9] or in lipoplexes for gene therapy [10,11]. It is also an integral ingredient of new surfactant-based highly stable vesicles [12].…”
Section: Introductionmentioning
confidence: 99%